Modeling and analyze a single-phase halbach magnetized tubular linear permanent magnet generator for wave energy conversion - Hamim, M.A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Malaysia is a country that is surrounded by numerous oceans that are able to be a renewable energy resource for betterment of human life. This research is proposed to design, model and analyze a portable single-phase linear permanent magnet generator for wave energy conversion (WEC) that is works with the local wave parameters. In comparison with a rotary generator, the linear generator is found preferable due to the direct-drive technology that promises low maintenance and cost. This research proposed three linear permanent magnet generator designs with different types of permanent magnet layout. The results show that proposed permanent magnet configuration is able to provide better flux density as compared to other proposed designs. Â© 2014 IEEE.